Bramante e Leonardo: classicismo e sperimentalismo alla corte di Ludovico il Moro (Quaderni di Gargnano, 2021)
The essay focuses on the role of Bramante and Leonardo during the XVth Century  at the fashionable court of Ludovico il Moro. At that time, florentine painters established the new classic style; by contrast, the Lombard School invented a new tradition, connected with the Paduan school. In this regard, The project of the central square of Vigevano created  by Bramante, has developed a more eccentric style, an alternative to Alberti’s ideas of Architecture. L’intervento puntualizza la nascita di una “scuola” regionale in Lombardia alternativa ai modelli classicisti fiorentini, grazie alla coeva presenza di Bramante e Leonardo. Lo sperimentalismo dei due maestri trova riscontri in diverse loro opere, dal San Gerolamo al Cenacolo, dall’Incisione Prevedari alla Sala delle Asse. Il progetto di Bramante per la piazza di Vigevano si inserisce all’interno di tale tradizione eccentrica e sperimentale, assai originale e all’avanguardia.
Keywords: Classicismo; Sperimentalismo; Bramante; Leonardo; Vigevano; prospettiva padana